2017
DOI: 10.5098/hmt.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Convective Boundary Condition on Nonlinear Thermal Convection Flow of a Micropolar Fluid Saturated Porous Medium With Homogeneous-Heterogeneous Reactions

Abstract: A numerical approach has been used to analyze the effects of homogeneous-heterogeneous reaction and nonlinear density temperature variation over a vertical plate in an incompressible micropolar fluid flow saturated Darcy porous medium. In addition, convective boundary condition is incorporated in a micropolar fluid model. The similarity representation for the set of partial differential equations is attained by applying Lie group transformations. The resulting non-dimensional equations are worked out numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The boundary value problem equations along with boundary conditions (18) convert into an initial value problem. With this method, we convert into a first‐order system of equations as follows: truelefttrue(trueleftf,fnormalI,fII,fIII,fIV,ϕ1,ϕ1normalI,ϕ2,ϕ2normalI,G,GnormalI,ψ,ψnormalI,ψIItrue)=true(truelefty1,y2,y3,y4,y5,y6,y7,y8,y9,y10,y11,y12,y13,y14true),f=y1,fnormalI=y2,fII=y3,fIII=y4,fIV=y5,italicfnormalV=1y1[y2y52y3y4]+Re(1+λ1)βy1(y1y4y2y3)1βy1cosθy5italicSt2…”
Section: Solution Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary value problem equations along with boundary conditions (18) convert into an initial value problem. With this method, we convert into a first‐order system of equations as follows: truelefttrue(trueleftf,fnormalI,fII,fIII,fIV,ϕ1,ϕ1normalI,ϕ2,ϕ2normalI,G,GnormalI,ψ,ψnormalI,ψIItrue)=true(truelefty1,y2,y3,y4,y5,y6,y7,y8,y9,y10,y11,y12,y13,y14true),f=y1,fnormalI=y2,fII=y3,fIII=y4,fIV=y5,italicfnormalV=1y1[y2y52y3y4]+Re(1+λ1)βy1(y1y4y2y3)1βy1cosθy5italicSt2…”
Section: Solution Of the Problemmentioning
confidence: 99%
“…Hayat et al have explained the effect of the homogeneous‐heterogeneous reactions on the unsteady incompressible flow of a Carreau fluid in a peristaltic channel with Hall current. Homogeneous‐heterogeneous chemical reaction effects on incompressible laminar flow towards the stagnation‐point of a Maxwell fluid over a moving sheet with consideration of heat source or sink were addressed by Khan et al RamReddy and Pradeepa have carried out a numerical solution to examine the strength of homogeneous and heterogeneous chemical reactions on the steady laminar incompressible flow of a micropolar fluid over a vertical plate in a saturated Darcy porous medium with convective boundary condition and also incorporated nonlinear thermal convection. Abd El‐Aziz and Saleem et al reported a magneto non‐Newtonian power‐law fluid model with the presence of an internal nonuniform heat source/sink.…”
Section: Introductionmentioning
confidence: 99%